ESTIMACIÓN DE LA EXPOSICIÓN LABORAL A LOS BIOAEROSOLES Y SU RIESGO EN LOS TRABAJADORES DE UN SISTEMA DE DISPOSICIÓN FINAL DE RESIDUOS SÓLIDOS EN EL DEPARTAMENTO DEL ATLÁNTICO (2017)
In a System of Final Disposal of Solid Waste, it is possible that the worker is exposed to biological agents, and therefore this can cause health conditions. There are currently no studies evaluating occupational exposure and its degree of biological risk in activities where they are managed in a way that does not deliberate biological agents, so there are no threshold values - TLV that allow to establish prevention measures, compared to other risks that If they have valuation criteria. However, there are methodologies that have been developed for its study, such as the Biogaval method and the Technical Standard of Prevention for biological agents. Simplified evaluation. In the present investigation, the estimation was made to the existing occupational exposure to bioaerosols and their degree of risk in the workers of a system of final disposition of solid waste in the municipality of Tubará-Atlántico, so that monitoring campaigns were carried out During a period of one (1) year, in two (2) morning and afternoon sessions. Four monitoring stations were located within the study area (Passive Cell 1, Passive Cell 2, Lixiviados Pool and Active Cell). The bioaerosols were collected using the six-stage Andersen Thermo Scientific waterfall impactor set, with an operating flow rate of 28.3 l / min for 5 minutes, located at a height of 1.5 m. Selective medium of Saboreaud Agar with dextrose to (2%) for the identification of bioaerosoles fungi. The maximum concentration of fungi bioaerosols was found in the active cell station, where the genus Aspergillus Sp was identified in the dry - rainy season, with the highest concentration of 5491.166 CFU / m3 and the highest concentration of Aspergillus fumigatus. In a lower concentration the Penicillium with 1823,321 UFC / m3. According to the results obtained, there is a probability that the emissions of funga bioaerosols generated in a non-deliberate way in the operations of the final disposal system of solid waste, put at risk the health of workers being vulnerable to obtaining a disease labor. However, further studies are required in the assessment of occupational risk to bioaerosols in outdoor environments.